Errors, error detection and correction efficiency in the container number code - Kiogora, Mutugi Praise; Loyford Njagi; Josephine Mutembei (African Journal of Science, Technology and Social Sciences, 2024)
The container number is an 11-digit code that uses a single parity check of modulo 11 to check the authenticity of the container numbers. The world relies on shipment containers to transport goods. Various types of cargos have been erroneously delivered in different places. The modulo 11 container number is divided into four parts. The owner code that consists of three capital letters of the Latin alphabet to indicate the owner or principal operator of the container. Such code needs to be registered at the Bureau International des Conteneurs in Paris to ensure uniqueness worldwide (per ISO 6346). The equipment category identifier consists of one of the following three capital letters of the Latin alphabet U for all freight containers, J for detachable freight container-related equipment, Z for trailers and chassis. The serial number consists of six numeric digits, assigned by the owner or operator, uniquely identifying the container within that owner/operator’s fleet. The check digit consists of one numeric digit providing a means of validating the recording and transmission accuracies of the owner code and serial number. The objective of this study is to determine the efficiency of the current modulo 11 container number in the error detection and correction. While the modulo 11 checksum calculation method is an effective way to detect errors in container numbers, it is not foolproof and errors can still occur. Modulo 11 container number code does not detect some transposition and substitution errors. The container number code and its check digit do not possess inherent error correction capabilities. This study therefore recommends a new modulo 13 container number code with higher error correction and detection capability.